2018
DOI: 10.1016/j.jevs.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Flunixin Meglumine on Pregnancy Rates in an Equine Embryo Transfer Program

Abstract: a b s t r a c tDuring the equine embryo transfer (ET), manipulation of the recipients cervix can stimulate the release of prostaglandin F2a by the uterine environment. Nonsteroidal antiinflammatory drugs such as flunixin meglumine (FM) are frequently used in order to prevent a potential luteolysis. However, despite the reduction of inflammatory reaction and release of prostaglandins, the benefits of FM in pregnancy rates (PRs) of mares submitted to ET are not conclusive, and there is no information about the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The embryos were collected on day 8 or 9 ater ovulation and were transferred into recipient mares that ovulated from one day before and up to ive days ater the donor mare, with the The reason for the signiicant improvement in recipient pregnancy rate using the Wilsher forceps-assisted transfer remains unknown. Manipulation of the cervix has been associated with prostaglandin release that may result in luteolysis and pregnancy failure, 14 or ejection of the embryo from the uterus through the cervix. 7 In 2016, McCue studied 218 recipient mare cycles, and measured serum progesterone in these mares at ive days ater ovulation.…”
Section: • Wilsher Forcep-assisted Transcervical Embryo Transfermentioning
confidence: 99%
See 3 more Smart Citations
“…The embryos were collected on day 8 or 9 ater ovulation and were transferred into recipient mares that ovulated from one day before and up to ive days ater the donor mare, with the The reason for the signiicant improvement in recipient pregnancy rate using the Wilsher forceps-assisted transfer remains unknown. Manipulation of the cervix has been associated with prostaglandin release that may result in luteolysis and pregnancy failure, 14 or ejection of the embryo from the uterus through the cervix. 7 In 2016, McCue studied 218 recipient mare cycles, and measured serum progesterone in these mares at ive days ater ovulation.…”
Section: • Wilsher Forcep-assisted Transcervical Embryo Transfermentioning
confidence: 99%
“…12 However, the relatively small percentage of recipient mares with low progesterone levels suggests that other factors such as poor embryo quality, post-transfer non-infectious or infectious endometritis, or failure of the maternal recognition of pregnancy by the recipient may better explain subsequent pregnancy rates. 14 Whether concurrent medication use increases pregnancy rates using conventional transfer is undecided. The study by Cuervo-Arango and others 13 reported a low but similar percentage of mares with signs of luteal failure in the conventional and Wilsher forceps-assisted transfer groups, suggesting that lower rates of luteal failure was not the cause of the improvement in recipient pregnancy rate.…”
Section: • Wilsher Forcep-assisted Transcervical Embryo Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…It has been estimated by the International Embryo Transfer Society that 44,906 embryo flushes and 26,145 transfers of fresh embryos were performed on horses worldwide in 2020 [7]. The pregnancy rate (PR) after transfer can range between 65% and 84%, with an incidence of early embryonic loss (EEL) before 50 days from 10 to 15.5% [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%